EXPLORING VARIOUS TOOLS AND RESOURCES THAT CAN ENHANCE LEARNING EXPERIENCES AND ENGAGEMENT AMONG STUDENTS - Kazakova Dilora Gaffarovna (Western European Studies, 2025)
This article talks about the application of technology in classrooms, highlighting various resources and tools utilized to enrich learning experiences as well as engagement of students. With the advancement of the digital world, teachers have many avenues to meet diversified learning needs and styles. Through an analysis of cutting-edge education technologies— ranging from interactive apps to virtual reality—this article attempts to provide insights into successful implementation strategies and the probable impact on student performance. The study shows that, when utilized cautiously, these technologies not only foster engagement but also provide a more individualized learning environment
Keywords: Educational technology; student engagement; interactive learning